The network structure of Chinese finance market through the method of complex network and random matrix theory. (14th August 2018) - Ji, Jian; Huang, Chuanchao; Cao, Ya; Hu, Sen
Summary: As we know, economic policy has a significant influence on the stock market. So, it should be interesting to detect the relation between the correlation structure of the stock market and economic policy. To achieve this target, the correlation matrix is analyzed through component analysis method first, to detect the economic implication of the components of correlation matrix. It is found that the biggest driving force of market behavior affects the whole stock market instead of individual stock or plate and the evolution of important plates of the second component relates closely to economic policies. Then, ordinary networks, denoising networks, and noise networks are constructed for different periods and distinction among the structures of different networks in the same period is analyzed. The result suggests that the economic factors corresponding to the first and second components make the stock market be sensitive and lead to a gathering effect in ordinary and denoising networks. At last, based on the inferences from this paper, the formation of power law in the stock network and the influence of crisis on the structure of stock network are discussed.